In-flow enantioselective homogeneous organic synthesis - Puglisi Alessandra (De Gruyter, 2021)
The use of enabling technologies, such as flow reactors, three-dimensional-printed devices, and electrochemistry, in the stereoselective synthesis of enantioenriched compounds is presented, with a special focus on the most significant contributions to the field reported in the last few years.